(untitled) (Architecture Image Studies, 2025)
The development of eco-friendly building materials capable of improving indoor air quality is essential. Although studies using photocatalysts have been conducted for this purpose, they have limitations in that their performance in adsorbing and decomposing harmful substances significantly declines in environments without light. To address this issue, this study evaluated the performance of cement board mixing graphite powder, which has physical adsorption performance, along with photocatalysts. Through preliminary testing, the replacement ratio of graphite and photocatalysts (TiO2, Recycled TiO2, and Mixing TiO2) was set at 10% by weight of cement. Comparative experiments were conducted based on the type of photocatalyst mixed with graphite in the cement boards. The test items included flexural failure load, impact resistance, fine dust adsorption, and CO2 adsorption. The experimental results showed that the flexural failure load and impact resistance for all three types met KS standards. For fine dust (PM2.5, PM10), and CO2 adsorption, the best performance was shown by recycled TiO2, Mixing TiO2, and TiO2, respectively, but the differences between them were minimal. Based on these results, it is concluded that the Mixture of graphite increases adsorption performance regardless of the type of photocatalyst used.